التيارات الثقافية في العصر العباسي ودور اهل البيت (ع) في مواجهتها (الامام الحسن العسكري انموذجا (مجلة كلية العلوم الاسلامية, 2020)
In mid 3rd century H . and exactly in the second Abbasid  era, Thereappeared ideological trends which are skeptical of Islamic religion depending upon the magic at one time , and Telmudi ideas at other times . The Muslim scholars , headed by Imam Al – Hasan Al – Askari , answerd them by Iogic and scientific arguments , relying on the gloroious  Qur an and the prophetic Sunnah ,and what He learnt from his grandparents . Therefore , He managed to take down their ideas in the bud and rescue the Islamic religion from anything irrelevant to what the prophet brought .